Synthesis of an organic metal nanoporous structure for controlled azathioprine delivery - Maghsoudloo, Maral; Abdouss, Majid; Kowsari, Elaheh (Nexo Revista Científica, 2021)
New drug delivery systems are highly efficient in diseases diagnosis and treatment and also controlled release of drugs. The use of this technology has given rise to the invention of new porous nanoparticles which are called metal organic frameworks (MOFs). In the present research, a kind of MOFs with formula Cu3(BTC)2 (HKUST-1, BTC ¼ benzene-1,3,5-tricarboxylate) with Fe3O4 magnetic nanoparticles (MNPs) as a core have been able to create three-dimensional magnetic porous structures. This magnetic and porous structure and the pores capability in being controlled have made these frameworks to be used as one of the best carriers in drug delivery. This system could magnetically be directed to the considered point inside body if it contains a drug that has side effects and may harm other body organs. Azathioprine is used in rheumatoid arthritis, granulomatosis with polyangiitis, Crohn's disease, ulcerative colitis, systemic lupus erythematosus, and in kidney transplants to prevent rejection. However, in the present work we consider the drug injection for kidney transplants to prevent rejection.